Absolute work function measurement by using photoelectron spectroscopy - Kim, Jeong Won; Kim, Ansoon (Current applied physics, 2021)
Work function (WF) of a material is not only an intrinsic characteristic of bulk but also a surface property. The measurement and control of WF have been of great concern in many electronic and optical devices as the WF governs charge transfer and charge injection/collection efficiency at interfaces and emission characteristics of conventional charged particle emitters. Photoelectron spectroscopy (PES) has been mainly used to determine surface electronic structure and chemical composition. Despite the common use of this technique to measure WF, there has been a lack of discussion on how to use the PES and what to be considered to determine the absolute WF. The main contribution of this review lies in the discussion of the causes of errors when measuring WF, and provides a guide for reliable WF measurement. Along with the limitations of current measurement technology, we propose future directions for absolute WF measurement. [Display omitted] •Definition of work function and applications in materials and devices.•Principles of absolute work function measurement by photoelectron spectroscopy.•Many factors to consider in measuring work function by PES.•Future expansion of the WF measurement technology.